To die or not to die: Regulatory feedback phosphorylation circuits determine receptor-interacting protein kinase-1 (RIPK1) function. (2nd January 2018) - Menon, Manoj B.; Gropengießer, Julia; Ruckdeschel, Klaus; Gaestel, Matthias
ABSTRACT: Complex posttranslational modifications determine the effects of receptor-interacting protein kinase-1 (RIPK1) on cell survival and death. Studies from us and others have revealed a p38 MAPK /MK2-dependent checkpoint in RIPK1 signaling. MAPKAP kinase 2 (MK2) phosphorylates RIPK1 to suppress RIPK1-mediated apoptosis and necroptosis in response to diverse stimuli relevant to inflammation, infection, genotoxic stress and chemotherapy.